2008
DOI: 10.2147/tcrm.s3126
|View full text |Cite
|
Sign up to set email alerts
|

Beclomethasone/formoterol fixed combination for the management of asthma: patient considerations

Abstract: Drugs for asthma and other chronic obstructive diseases of the lungs should be preferably delivered by the inhalation route to match therapeutic effects with low systemic exposure. Inhaled drugs are delivered to the lungs via different devices, mainly metered dose inhalers and dry powder inhalers, each characterized by specifi c inhaler technique and instructions for use. The patient-device interaction is part of the prescribed therapy and can have a relevant impact on adherence and clinical outcomes. The most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…The effectiveness of the lower ICS dose in BDP/FF may be due to the extra-fine formulation that allows homogeneous distribution of the two drugs throughout the bronchial tree [ 31 ] entailing a greater efficacy per microgram of ICS, in agreement with previous studies on asthma [ 32 - 34 ]. The extra-fine BDP/FF formulation allows the treatment of both large and small airways; the latter are particularly relevant in COPD pathophysiology [ 35 ].…”
Section: Discussionsupporting
confidence: 66%
“…The effectiveness of the lower ICS dose in BDP/FF may be due to the extra-fine formulation that allows homogeneous distribution of the two drugs throughout the bronchial tree [ 31 ] entailing a greater efficacy per microgram of ICS, in agreement with previous studies on asthma [ 32 - 34 ]. The extra-fine BDP/FF formulation allows the treatment of both large and small airways; the latter are particularly relevant in COPD pathophysiology [ 35 ].…”
Section: Discussionsupporting
confidence: 66%
“… 57 Nicolini and colleagues have shown that the small particle (~1.5 microns) combination therapy of ICS/LABA (BDP/Form) delivered from an HFA-solution pMDI achieved 2/3rd central airways deposition and 1/3rd peripheral airways deposition. 58 Recently, Scichilone and colleagues have replicated this distribution in the regional airways distribution of 2/3rd central and 1/3rd peripheral, for the same combination therapy of ICS/LABA (BDP/Form) delivered from a novel DPI, where the inhaler device also generates small particle (~1.5 microns) sized aerosols. 59 Hence, the development of inhalers delivering small particle aerosols now allows us to achieve deposition to treat the whole airway tree; that is, simultaneously targeting drug to the large and also the small airways.…”
Section: Introductionmentioning
confidence: 87%
“… 52 , 53 , 54 , 55 , 56 , 57 The capability to generate small particle aerosols of ICS and LABA has been utilised to improve the total lung dose of delivered drug to levels between 30 to 50%, which is a significant improvement compared to conventional devices. 56 , 57 , 58 , 59 , 60 Of greater significance is that these small aerosol particles are able to effectively deliver inhaled drug to the periphery of the lungs.…”
Section: Introductionmentioning
confidence: 99%